Ultrasonography of urinary system in normal Iraqi buffaloes (Bubalus bubalis): Osamah Muwaffag Al-Iraqi¹, Salim Hamad Dhahir² and Adeeba Younis Shareef³ - Al-Iraqi, Osamah Muwaffag (The Iraqi Journal of Veterinary Medicine, 2018)
The objective of this study was to evaluate the usefulness of ultrasound in the examination of urinary system in buffaloes. Ultrasonography of the urinary system was done for 60 local buffaloes breed, 1-15 years old of both sexes in Mosul/Iraq, and they then were divided into two groups according to age, 25 calves less than 2 years and 35 adults 2-15 years. Kidney measurements are taken from three different sites (right lumbar, right sublumbar and right twelfth intercostal space. The right sublumbar region is the best area for getting good ultrasonographic images (in both adult and calves) followed by right lumbar region which gives clear images in adult buffaloes. Ultrasonographic examination for the left and right kidneys in adult buffalo and their calves showed no significant difference in kidney measurements from different sites (lumbar, sublumbar, twelve intercostal space). The results showed that the mean thickness of right kidney of buffaloes aged 2-15 years from right sublumbar region was (7.40±0.13) centimeters and in buffalo calves was (5.29±0.23) cm. The mean thickness of left kidney of buffaloes from right sublumbar region was (7.30±0.20) cm, and in buffalo calves was (5.06±0.59) cm. The urinary bladder is easily observed by ultrasonography per-rectum in adult and percutaneous in calves (right sublumbar region). The urinary bladder appears as circumscribed round to oval structure in the pelvic area. It usually contains anechoic to hypoechoic urine. The wall of urinary bladder is echogenic, smooth and its thickness varies with the amount of bladder distention. Positive correlation between right kidney thickness (cm) (from right sublumbar region) and the age (months) for buffaloes (0.627).